In Vitro and In Silico Study of Immobilized Xylanase from Trichoderma viride using Bentonite Matrices Activated with HCl - Nur Lailah; Sasangka Prasetyawan; Arie Srihardyastutie (The Journal of Pure and Applied Chemistry Research, 2017)
The purpose of this study was aimed determine the optimum conditions of agitation time and concentration of immobilized xylanase by in vitro and in silico and efficient reuse of immobilized xylanase. The results of in silico test showed that xylan bounded on the residues of xylanase active site through hydrogen bonding with the amino acid glutamic 177A, glutamate 86A, tyrosine 88A, arginine 122A, and glutamine 136A, whereas bentonite and the residues of xylanase active site form hydrogen bonding with the amino acid glutamine 52, arginine 81, isoleucine 128 and glycine 130. The results of in vitro study showed that the optimum condition of xylanase immobilization was achieved at agitation time of 3 hours with the amount of xylanase adsorbed was 12.593 mg/g bentonites and activity of 50.328 units and the concentration of immobilized xylanase of 4.259 ppm and the amount of xylanase adsorbed of 16.162 mg/g bentonites and activity of 56.362 units. The immobilized xylanase can be used as many as five repetitions with the residual enzyme activity of 60%.